A lógica do neoliberalismo no documento "Melhores práticas em escolas de ensino médio no Brasil": uma cartografia - Silva, Rosanna Maria Araújo Andrade (Universidade Federal de São Carlos, 2022)
The present research intends to map characteristic traces of the organizational changes occurred in educational instituitions, especially brazilian ones, in the last decades of 20th century. The present investigation’s emphasis is to study how the capitalist’s logic, throughout the neoliberalism, proliferates in the educational systems. The investigation originally came from a analysis of the statements contained in a educational document, and after that it were established the conetions with other contexts, thus revealing a mundial tendency. The document in question, which title is “Melhores Práticas em Escolas de Ensino Médio no Brasil”, is a research report carried out by Instituto Nacional de Pesquisas Educacionais Anísio Teixeira (a federal autarchy associated with Ministry of Education) in partnership with Inter-american Development Bank, in 2010. The research was divided in three investigative dimentions: documental, historical-sociological and philososophical. The document’s internal problems guided the establishment of the references for analysis. From the historical-sociological perspective, the research was supported by Christian Laval’s analysis, in his book School is not an enterprise: the neoliberalism assaulting public education, in which the sociologist traces the problematic contours of neoliberalism’s influence in the educational systems. From the philosophical perspective, the analysis was based in Gilles Deleuze’s diagnosis, in Post-scriptum about the control societies, a text in which the philosopher describes how the passage from disciplinary societies to control societies produces institutional and subjectives transformations. This mutation of domination forms, described by Deleuze, is strongly related to a technological transformation: the emergency of information technologies. The analysis was conducted by what we called cartographical method. This one was inspired by the concept of cartography, developed by Deleuze and Guattari in A thousand plateaus. We concluded that the contemporary transformations can be understanded as a result of a capitalist axiomatics’ rearticulation. In this new mode of realization, the institutional school’s specificity is deterritorializated, to be reterritorializated in the enterprise form. The school loses its relative autonomy to economical field, that is characteristic of the disciplinary regime, and starts to compose directly the financial capitalisms’ informational flows. In this paradigm, educational is no longer seem as a right, but as a merchandise. This conception implies a destruction of the school’s anthropological function – insert the new generations in a common symbolic universe. We understand that it is a scientific’s research duty to contest the doxa of its field in a determined historic moment. Therefore, we question education’s representation as a merchandise, and we reaffirm school’s specificity and the institutional function in ensuring the universal right to culture.
Neoliberalism’s logic in the document “Melhores práticas em escolas de ensino médio no Brasil”: a cartography
Keywords: Ensino médio; Neoliberalismo; Axiomática capitalista; Cartografia; Avaliação; High school; Neoliberalism; Capitalist axiomatics; Cartography; Evaluation; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM